Proposed Strategy Marketing for Trees Cafe - Pasaribu, Juwita Carolina; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2013)
The growth of cafe and restaurant business in Bandung indicates a significant increase every year. This happens as part of the culinary city's identity that attached to Bandung. Trees Cafe is one of the cafe that is located in Bungur, Karang Setra Bandung. Since its establishment in September 2009 to the present the income of the cafe has not made a significant progress and the sales never reach the target.With the tighter competition among cafe and restaurant in Bandung, it leads to the stagnant of Trees Cafe sales. This is due to the lack of promotion and proven by the unstable in sales income so the monthly sales target is not fulfilled. The focus of this research is to find a solution that can help Trees Cafe to increase its sales income by attracting the customer to come. Internal analysis, brand analysis, external analysis, situation analysis and sampling to the customer is needed to be done to get the root cause of Trees Cafe’s problem. Keywords: Bandung, cafe, restaurant, marketing strategy, brand awareness, promotion